Kajian Pembaharuan Hukum Dalam Asuransi E-Commerce - Fiqqih Anugerah; Hari Sutra Disemadi (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
Insurance in the electronic trading business has been regulated by law in Indonesia, but there are technical obstacles related to electronic trade insurance in the Indonesian legal system in its application. When insurance is used in business through e-commerce, there is legal protection for the insurer regarding the obligation to notify the policyholder about the subject of insurance, and legal protection for the policyholder regarding the purpose of the policy, namely the transfer of risk to compensation for the damage caused by the event, as well as the risk against risks that threaten insurance coverage. Therefore, this study aims to disseminate knowledge about how insurance arrangements for e-commerce businesses are from a legal point of view in Indonesia and what are the reasons for e-commerce insurance to be specifically regulated by Indonesian law. This study uses a normative legal research method through library research tracing guidelines such as laws, articles, or journals related to the themes and titles to be studied which will be used as the basis or foundation for the preparation of this article. The results of this study indicate that insurance agreements can be used to mitigate risks that may arise from the intrusion of third parties into the e-commerce protection system, as long as the agreement does not violate the insurance principles as regulated in Indonesian legislation.